Bullosis Diabeticorum: Rare Presentation in a Common Disease - Vineet Gupta; Neha Gulati; Jaya Bahl; Jaswinder Bajwa; Naveen Dhawan (Case Reports in Endocrinology)
A 27-year-old African American male presented with a sudden onset of blisters. He had a past medical history of uncontrolled diabetes mellitus type I, diabetic vasculopathy, and neuropathy. The physical examination revealed nonerythematous skin denudations on both elbows and lateral aspect of arm bilaterally. Investigations which included skin biopsies confirmed the diagnosis of bullosis diabeticorum. The bullae were treated with hydrotherapy and healed with no complications in 4 weeks. We present this case to illustrate the rare occurrence of diabetic bulla in a diabetic patient especially with poor glycemic control. The case is also a reminder of the importance of diabetes screening in nondiabetic patients who are diagnosed with diabetic bulla.